Given:
Common ratio=-3
11th term=11
To determine the 13th term, we first note the geometric sequence formula:
![a_n=ar^(n-1)](https://img.qammunity.org/2023/formulas/mathematics/college/ap7tka3z5szz7gan7yzwlm8df4q559etdo.png)
where:
a=1st term
n=nth term
Since the 11th term is 11, we can solve the first term by following the process as shown below:
![\begin{gathered} a_(n)=ar^(n-1) \\ a_(11)=a(-3)^(11-1) \\ 11=a(-3)^(10) \\ Simplify \\ a=(11)/(59049) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/c039m3fqhsq4k0tciae7qdbmsfmxmndugd.png)
Next, we plug in a=11/59049 when n=13:
![\begin{gathered} a_(n)=ar^(n-1) \\ a_(13)=((11)/(59049))(-3)^(13-1) \\ Calculate \\ a_(13)=99 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/e65jwhf5wj2g6i9vcrtbcqwhh8rbbf9273.png)
Therefore, the answer is: 99